Current concepts and progress in RSV vaccine development - Guvenel, Aleks K (Expert Rev Vaccines, 2014)
Respiratory syncytial virus (RSV) disease is an important cause of morbidity and mortality in children and debilitated adults and remains one of the major global unmet challenges for vaccine development. Several immunological issues have delayed the development of vaccines, especially the poorly protective response to natural infection and the enhancement of disease following administration of formalin inactivated vaccines during trials conducted in the 1960s. Advances in knowledge of the immune system, of the virus and its antigenic properties combined with new vaccine technologies are now injecting new hope into the field and have given rise to many promising vaccine approaches. Some of these may be optimal for use in children, while others may be more appropriate for pregnant women or vulnerable older adults. With a multi-pronged approach to prevention, we propose that it may be possible to destabilise community circulation of RSV and thus to significantly lessen the impact of RSV disease.